Selective of IoT applications for water quality monitoring in Malaysia - Zainuddin, Ahmad Anwar; Amir Hussin, Amir 'Aatieff; Annas, Ammar Haziq; Bharudin, Mohamad Syafiq Asyraf; Abdul Rajat @ Abdul Razak, Alin Farhain; Mahazir, Muhammad Nur Badri; Ahmad Puzi, Asmarani; Handayani, Dini Oktarina Dwi; Abdul Raziff, Abdul Rafiez (IIUM Press, 2024)
The aquaculture industry in Malaysia relies predominantly on Recirculating Aquaculture Systems (RAS), which are susceptible to infections, leading to disease outbreaks and significant economic repercussions. The frequent need for manual interventions makes RAS labor-intensive and inefficient. To address these challenges, this study advocates a shift towards disease prevention and proactive water quality management. The proactive approach entails modern water treatment methods, stringent biosecurity measures, and the integration of IoT (Internet of Things) technology to anticipate and prevent disease outbreaks. Our disease detection system utilizes real-time sensors, machine learning algorithms, and IoT technology to swiftly identify pathogen indicators. Simultaneously, the IoT-enabled water quality monitoring system consistently delivers crucial data, eliminating the need for on-site monitoring. The adoption of disease prevention and control strategies, including probiotics, vaccinations, and biosecurity measures, plays a pivotal role in fostering sustainable advancements within the aquaculture sector. By incorporating effective water quality management, optimizing fish stocking density, ensuring proper nutrition, adhering to hygienic practices, and deploying fish vaccines, with the aim to mitigate the occurrence of fish diseases, ultimately bolstering the resilience and sustainability of Malaysia's aquaculture industry. Overall, this paper proposes a comprehensive overview of IoT-based applications for water quality monitoring in Malaysia’s aquaculture with the advancements in IoT technology and its potential impact on improving water quality management practices.